Design and synthesis of pyrazole–pyrazoline hybrids as cancer‐associated selective COX‐2 inhibitors. Issue 1 (4th October 2020) - Akhtar, Wasim; Marella, Akranth; Alam, Mohammad Mumtaz; Khan, Mohemmed F.; Akhtar, Mymoona; Anwer, Tariq; Khan, Farah; Naematullah, Md.; Azam, Faizul; Rizvi, Moshahid A.; Shaquiquzzaman, Mohammad
Abstract: In continuation of our previous work on cancer and inflammation, 15 novel pyrazole–pyrazoline hybrids (WSPP1 –15 ) were synthesized and fully characterized. The formation of the pyrazoline ring was confirmed by the appearance of three doublets of doublets in 1 H nuclear magnetic resonance spectra exhibiting an AMX pattern for three protons (HA, HM, and HX ) of the pyrazoline ring. All the synthesized compounds were screened for their in vitro anticancer activity against five cell lines, that is, MCF‐7, A549, SiHa, COLO205, and HepG2 cells, using the MTT growth inhibition assay. 5‐Fluorouracil was taken as the positive control in the study. It was observed that, among them, WSPP11 was found to be active against A549, SiHa, COLO205, and HepG2 cells, with IC50 values of 4.94, 4.54, 4.86, and 2.09 µM. All the derivatives were also evaluated for their cytotoxicity against HaCaT cells. WSPP11 was also found to be nontoxic against normal cells (cell line HaCaT), with an IC50 value of more than 50 µM. The derivatives were also evaluated for their in vitro anti‐inflammatory activity by the protein (egg albumin) denaturation assay and the red blood cell membrane stabilizing assay, using diclofenac sodium and celecoxib as standard. Compounds that showed significant anticancer and anti‐inflammatory activities were further studied for COX‐2 inhibition. The manifestation of a higher COX‐2 selectivity index of WSPP11 as compared with other derivatives and an in vitro anticancer activity against four cell lines further established that compounds that were more selective toward COX‐2 also exhibited a better spectrum of activity against various cancer cell lines. Abstract : Fifteen novel pyrazole–pyrazoline hybrids (WSPP1 –15 ) were synthesized, characterized, and tested for their growth inhibitory activity against five cancer cell lines. Compounds that showed significant anticancer and anti‐inflammatory activities were further studied for COX‐2 inhibition. Compounds, like WSP11, which were more selective toward COX‐2, also exhibited a better spectrum of activity against various cancer cell lines.